Short-term in-season ballistic training improves power, muscle volume and throwing velocity in junior handball players. A randomized control trial - Bouagina, Rachid; Padulo, Johnny; Fray, Akram; Larion, Alin; Abidi, Hatem; Chtara, Mokhtar; Souhail Chelly, Mohamed; Khalifa, Riadh (Biology of Sport, 2022)
This study investigated the effects of a ballistic training programme using an arm/shoulder specific strength device (ASSSD) on the upper body peak power (PP), muscle volume (MV) of the dominant arm and throwing velocity in junior handball players. Twenty-six players were randomly assigned to an experimental (EG = 15, age 17.6 ± 0.51 years) and control (CG = 11, age 17.36 ± 0.50 years) group. Over an 8-week inseason period, the EG performed a ballistic training programme (2 sessions/week) immediately before their normal team handball training. Both groups underwent tests on the ASSSD, which operates in consecutive accelerative and decelerative actions, for throwing characteristics determination. Peak power (PP), peak force (PF), peak velocity (PV), peak rate of power development (PRPD), muscle volume (MV), throwing velocity with runup, standing throw, and jump throw were also assessed before/after the training programme. The EG group showed significant post-training improvements in PP (52.50% – p < 0.001), PF (26.45% – p < 0.01) and PRPD (78.47% – p 0.05, respectively). There was also a post-training improvement in the velocity at PP (22.82% – p < 0.001) and PF (42.45% – p 0.05 respectively). There was a significant increase in acceleration at PP (51.50% – p < 0.01) and PF (69.67% – p < 0.001). MV increased (19.11% – p < 0.001) in the EG, with no significant change (3.34% – p = 0.84) in the CG. Finally, significant increases were obtained in the three throw types (3.1–6.21%, p < 0.05- < 0.001) in the EG compared to the CG. The additional ASSSD training protocol was able to improve muscle strength/volume and ball throwing velocity in junior handball players.